Awareness and Training in Cybersecurity at Universities in Bulgaria. Compliance with ISO 27001 - Pavlova, Elitsa (Research Papers, 2025)
This study examines the current state of cyber security awareness and training in universities in Bulgaria, with an emphasis on compliance with ISO 27001 standards. As digitization increases, the need for robust cyber security measures becomes critical. The findings reveal varying levels of awareness and preparedness regarding cybersecurity threats, along with a lack of standardized training programs. Compliance of existing practices with ISO 27001 requirements was assessed and gaps in policy implementation and employee training identified. Recommendations for improving cybersecurity education are provided, emphasizing the importance of a proactive and comprehensive approach to cybersecurity in educational institutions.
Keywords: Higher education; Information security; Awareness and online learning; ISO 27001